Strategi Kualitas Air Pertumbuhan K.Alvarezii Dan E.Dencitulatum yang Dibudidaya Pada Perairan Desa Lagaruda Kabupaten Takalar - Said, Ahmad Ihsan; Anwar, Kasful; Ridhowati, Sherly (Universitas Batangahari Jambi, 2025)
Seaweed is one of the leading aquaculture commodities that has significant economic value, both in the domestic and international markets. The types of seaweed that are widely cultivated in Indonesia are Kappaphycus alvarezii and Eucheuma denticulatum. This study aims to analyze the strategic growth of Kappaphycus alvarezii and Eucheuma denticulatum seaweed cultivated in the same waters in Lagaruda Village, Sanrobone District, Takalar Regency. The research method used an descriptive analysis using SWOT based on primary data using questioner and interview. Therefore, the integration of both types of seaweed can be an alternative strategy to increase the productivity and sustainability of seaweed cultivation in the coastal area of Takalar. Pengembangan Berdasarkan analisis SWOT dengan posisi strategis di kuadran SO (0,98; 1,31), strategi pengembangan yang optimal adalah: E. denticulatum sebagai komoditas volume dengan pertumbuhan cepat dan produktivitas tinggi, serta K. alvarezii sebagai produk premium.